Tax Competition and Income Sorting: Evidence from the Zurich Metropolitan Area - Christoph A. Schaltegger; Frank Somogyi; Jan-Egbert Sturm (Center for Research in Economics, Management and the Arts (CREMA), 2009)
In this paper, we provide empirical evidence for the influence of income taxes on the choice of residence of taxpayers at the local level. The fact that Swiss communities can individually set tax multipliers thereby shifting the progressive tax scheme which is fixed at the cantonal (state) level enables us to study the effect of differences in income taxation on individuals' choice of location within an economically and culturally homogeneous region. Using panel IV regressions covering the years 1991-2003 and 171 communities in the Swiss canton of Zurich and spatial error regressions for the 171 communities in 2003, we find substantial evidence for income sorting.
Keywords: H71; H73; R50; 330; tax competition; fiscal federalism; income segregation; income tax